ETIKA ANAK BANGSA PERSPEKTIF PANCASILA - Abdul Basir Solissa (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2020)
Pancasila as the basis of the State, the state ideology, and the nation's view of life are national agreement and national compromise of various interest groups. Pancasila was agreed as a final meeting point, therefore Pancasilamust be the starting pointin overcoming all problems of national and state life.One of the complicated problems that are currently happening is Indonesian community behavior that is already not in line with the Pancasila values.In this context Pancasila must be placed not only as the basis of the State, the state ideology, and the nation's view of life, but also must be the basis of ethics, the value standard, and the moral standards. This article examines the three main areas that become the pulse of the life of the nation, that is politics, economics and social media.The behavior of the Indonesian community in the three main streams, read from the Pancasila perspective, therefore expected to give birth to a new awareness in the rule of a nation which is more balanced, humane and enlightening.